A nanovehicle developed for treating deep-seated bacteria using low-dose X-ray. (1st January 2017) - Pan, Chien-Lin; Chen, Ming-Hong; Tung, Fu-I; Liu, Tse-Ying
Graphical abstract: Abstract: Many non-antibiotic strategies, such as photocatalysis and photodynamic therapy, have been proposed to inhibit and/or kill bacteria. However, these approaches still have drawbacks such as insufficient bacterial specificity and the limited penetration depth of ultraviolet and near-infrared light. To overcome these limitations, we developed a bacteria-specific anti-bacterial technique via using low-dose X-ray. Graphene oxide quantum dots (GQDs, a multifunctional vehicle) conjugated with vancomycin (Van, a bacteria-targeting ligand) were assembled with Protoporphyrin IX (PpIX, a photo/radiation sensitizer) to yield a novel Van-GQDs/PpIX complex that specifically attached to Escherichia coli and efficiently generated intracellular reactive oxygen species following X-ray activation. Delivery using GQDs increased the PpIX/Van ratio in the target bacterial cell, damaged bacterial cell wall, and enhanced X-ray-induced PpIX activation. Hence, this approach allowed for the use of a low-dose X-ray to efficiently activate the Van-GQDs/PpIX complex to exert its bactericidal effects on Escherichia coli without damaging normal cells. Furthermore, the E. coli did not develop resistance to the proposed approach for at least 7 rounds of repeated administration during one week. Thus, this proposed vehicle exhibiting bacteria-specific X-ray-triggered toxicity is a promising alternative to antibiotics for treating serious bacterial infections occurring in deep-seated tissues/organs (e.g., osteomyelitis and peritonitis). Statements of Significance: Administration of antibiotics is the most common treatment modality for bacterial infections. However, in some cases, patient attributes such as age, health, tolerance to antibiotics do not allow for the use of high-dose antibiotics. In addition, some bacteria develop resistance to antibiotics because of improper and long-term use of these agents. Therefore, non-antibiotic strategies to treat deeply situated bacterial infections, such as osteomyelitis, are urgently needed for avoiding amputation. To date, several non-antibiotic approaches, such as Ag nanoparticles, graphene-based materials, photocatalysis, and photodynamic therapy have been proposed to inhibit and/or kill bacteria. However, the major challenges of photochemical strategies, specificity and limited penetration depth of light source, still remain for treating the deep-seated bacteria. To overcome these problems, we developed a novel nanovehicle that exerted toxic effects specifically on bacteria following activation by a deeply penetrative low-dose X-ray, without damaging normal cells. As such, it realizes a deeply photochemical route for treating the deep-seated bacteria.